2017
DOI: 10.1177/0954405416687146
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigations on springback in V-bending of tailor-welded blanks of interstitial free steel

Abstract: Tailor-welded blanks of interstitial free steel are commonly used in complex automotive skin panels. The presence of weld zone, difference in thickness and high anisotropic behaviour affect forming behaviour of tailor-welded blanks significantly. Therefore, incorporation of anisotropy of the sheets and properties of the weld zone in finite element simulations is very important for accurate prediction of springback in bending of tailor-welded blanks. In this study, experimental and finite element simulations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…According to equations (6) and (9), the distribution of tangential stress, s u , in the plastic deformation zone can be expressed as follows…”
Section: The Von Mises Criterion Is Used For Plastic Yieldingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to equations (6) and (9), the distribution of tangential stress, s u , in the plastic deformation zone can be expressed as follows…”
Section: The Von Mises Criterion Is Used For Plastic Yieldingmentioning
confidence: 99%
“…7 Plastic deformations in each bending step result in residual stresses and strains, which may potentially affect the determination of forming parameters and bending path. However, most of the current research focused on the study of springback behavior in bending process, [8][9][10][11] and the residual stresses and strains caused by cold bending process have not been paid enough attention. Therefore, it is of importance to predict residual stresses and strains of the formed plates in the forming process.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the simulation results, various parameters can be modified to verify their effect on the output data. [39][40][41][42] Figure 12 shows the FE model for Hecker's punch stretching tests of boron steel (22MnB5) sheets. Specifically, reduced-integration four-node linear shell elements (S4R) are utilized for the blank.…”
Section: Fe Simulationsmentioning
confidence: 99%
“…For the GTAW process, Goldak double ellipsoidal source was implemented for getting an accurate result. It is observed that most of the studies discussed are repeatedly focused on Al and steel materials [10][11][12]. This makes a great deal to study the manufacturing of titanium and its alloy-based TWB as they are widely used in aerospace and defense applications [13][14][15].…”
Section: Introductionmentioning
confidence: 99%